NMDA and AMPA receptors mediate intracellular calcium increase in rat cortical astrocytes - HU Bo; SUN Sheng-gang; TONG E-tang (Acta Pharmacologica Sinica, 2016)
AIM: To study the effect of glutamate on the intracellular calcium signal of pure cultured rat astrocytes and the role of N-methyl-D-aspartate (NMDA) and alpha-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid (AMPA) receptors in the procedure. METHODS: The fluorescence of calcium was measured by Fura-2/AM (F(345)/F(380)). RESULTS: L-Glutamate induced [Ca(2+)](i) increase in most of the cells in concentration- and time-dependent manner. NMDA 50 mmol/L induced the fluorescence increase by almost three to four times, while the effect of AMPA 50 mmol/L was just half of that of D-(-)-2-amino-5-phosphonopentanoic acid (D-AP-5; a selective antagonist of the NMDA receptor). 6-Cyano-7-nitroquinoxaline-2,3-dione (CNQX, a selective antagonist of the AMPA receptor) abolished the effects of NMDA and AMPA, respectively. D-AP-5 and CNQX simultaneously or respectively attenuated the effect of L-glutamate at different degrees, but could not abolish it entirely. CONCLUSION: Glutamate modulated intracellular Ca(2+) of pure cultured rat astrocytes through different pathways. The activation of NMDA and AMPA receptors took part in the complex mechanisms.